Comparison of the coal dust suppression performance of surfactants using static test and dynamic test. (15th December 2021) - Zhao, Zidong; Chang, Ping; Xu, Guang; Ghosh, Apurna; Li, Danqi; Huang, Jinxin
Abstract: Coal dust has a significant impact on miners' health, leading miners to have the most common occupational disease, Coal Workers' Pneumoconiosis. Water spray with surfactants is one of the most effective methods for dust control in underground mines. Different types of surfactants have different impacts on coal dust suppression efficiency. The evaluation of surfactants for coal dust suppression is important and can be categorized into two groups being the static tests and the dynamic tests. Previous studies have applied the static tests the most rather than the dynamic tests due to the complication of application. However, some studies showed that dynamic tests are more reliable to evaluate the surfactants' performance. The aim of this study is to compare and analyze whether the results from static tests and dynamic tests are consistent for surfactants evaluation in terms of coal dust suppression. Different types and concentrations of surfactants were considered in experiments. It was found that the results from static tests were not consistent with dynamic tests. Moreover, although the surface tension was highly correlated with the sink time showing in some surfactants, it was not applicable for all surfactants. Most importantly, due to many factors such as airflow and foam generation that were taken consideration in dynamic tests, it could be more reliable and accurate considering the discrepancies existing between static and dynamic tests. The results of this study could be applied to determine the evaluation methods of surfactants for coal dust suppression.